Influence of Different Counterfaces on Tribological Behaviors of Al2O3 Nanocomposites for Joint Prostheses - Carlos Morillo (Japanese Society of Tribologists, 2009)
Alumina has been widely used in joint prostheses due to its excellent biocompatibility, wear and corrosion resistance, low friction, high mechanical strength and low cost. However, the further improvement in fracture toughness and wear resistance is required for severe activities. In this work Y-TZP (100 nm), TiO2 (50 nm), were added to Al2O3 powder (300 nm) to prepare new candidate composite materials for prostheses. These starting powders were mixed and hot pressed. Mechanical properties as Vickers hardness and fracture toughness were estimated using the indentation method. Wear tests were carried out in a ball-on-plate tribometer, with a frequency of 1 Hz, a load of 49 N, for 4h. Alumina and silicon nitride balls were used as counterfaces. Distilled water and Fetal Bovine Serum Solution were used as environment. Lowest specific wear rate was about 10-8 mm3/Nm and lowest coefficient of friction was around 0.2 for the case of silicon nitride ball. Furthermore the chemical species formed on the surface were studied.